Department of Geophysics - Jarzyna, Jadwiga; Dec, Jerzy; Wawrzyniak-Guz, Kamila (Geology, Geophysics and Environment, 2016)
Department of Geophysics is one of 8 independent units at the Faculty of Geology Geophysics and Environmental Protection.